1990
DOI: 10.2514/3.25156
|View full text |Cite
|
Sign up to set email alerts
|

Leading-edge vortices due to low Reynolds number flow past a pitching delta wing

Abstract: Flow past a pitching delta wing is examined in a water channel for a range of mean angle of attack. The wing is perturbed sinusoidally over a tenfold range of reduced frequency, in order to determine the nature of the vortex development and breakdown. There occur two basic types of vortex development: at low frequencies, the vortex core develops in the upstream direction towards the apex; at high frequencies, there is ejection of the leading edge of the vortex core from the apex in the downstream direction. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 13 publications
3
7
0
Order By: Relevance
“…This amplitude attenuation is similar for both the slender and nonslender wings. This observation is also similar to the findings of previous investigations for unsteady wings [21][22][23][24][25].…”
Section: A Periodic Trailing-edge Blowingsupporting
confidence: 93%
See 2 more Smart Citations
“…This amplitude attenuation is similar for both the slender and nonslender wings. This observation is also similar to the findings of previous investigations for unsteady wings [21][22][23][24][25].…”
Section: A Periodic Trailing-edge Blowingsupporting
confidence: 93%
“…It can be observed that X bd =c and C N exhibit similar trends of increasing with increasing f . This is similar to the findings of previous investigations for unsteady wings [21][22][23][24][25]. The phase lag b of X bd =c for the slender delta wing is comparable to those of the nonslender delta wing.…”
Section: A Periodic Trailing-edge Blowingsupporting
confidence: 89%
See 1 more Smart Citation
“…7 In the event that the delta wing undergoes unsteady motion, the nature of the vortex breakdown is altered. The most predominant feature is a phase shift between the motion of the wing and the onset of breakdown, as shown by Woffelt, 8 Gilliam et al, 9 Reynolds and Abtahi, 10 Hudson et al, 11 Thompson, 12 Magness et al, 13 Atta and Rockwell, 14 LeMay et al, 15 Jarrah, 16 Ashley et al, 17 and Rockwell;18 all of the foregoing investigations have been for pitching motion. Analogous types of phase shift of breakdown occur for rolling motion of the wing as shown by Hanff and Huang, 19 Ng et al, 20 and Cipolla et al 21 Conceptual features of the complex nature of vortex breakdown, interpreted in the context of experiments, theory, and numerical simulations are provided by the reviews and assessments of Sarpkaya, [22][23][24] Hall,25 Liebovich, 26,27 Escudier, 28 Brown and Lopez, 29 Lopez and Perry, 30 Delery, 31 and Wang and Rusak.…”
Section: Introductionmentioning
confidence: 90%
“…Recent investigations have focussed on visualization of the vortex breakdown phenomenon during sinusoidal (Woffelt 1986, Atta andRockwell 1990) and ramp pitching Abtahi 1987, Magness et al 1989) motions. All of these studies have shown a lag in the location of vortex breakdown with respect to the motion of the wing.…”
Section: Introductionmentioning
confidence: 99%